The Role of Competition Law in Encouraging Innovation and Competitiveness of Companies in West Java - Nasution, Emmi Rahmiwita; Siburian , Henry Kristian; Judijanto, Loso; Sugianto, Efendi (West Science Law and Human Rights, 2023)
This study explores the complex relationships that exist between innovation, competitiveness, and competition legislation in West Java, Indonesian businesses. West Java's varied industrial landscape makes it a perfect place to study how competition legislation influences creativity and competitiveness. Using a mixed-method approach, the study combines survey data that is quantitatively collected with qualitative information obtained through interviews. The results show that a sizable majority of West Javan businesses have a favorable opinion of competition legislation and see it as a tool for ensuring openness and fair competition. Notably, a significant fraction of these businesses also devote a notable amount of their resources to research and development (R&D) and actively participate in innovation activities. According to the survey's findings, firms may be encouraged to invest in innovation by competition laws that are properly implemented, which is consistent with neoclassical economic theory. In spite of the favorable attitudes and investments in innovation, there are differences amongst West Javan enterprises in competitiveness metrics like market share and profitability. This highlights the intricate connection—which varies depending on the sector and industry—between company competitiveness and competition legislation. Qualitative insights gleaned from interviews shed light on the dynamics and obstacles unique to the industry, highlighting the necessity of customized strategies for competition law enforcement. The paper also outlines obstacles, including a lack of knowledge about competition law among enterprises, resource limitations that regulatory bodies must deal with, and worries about intellectual property protection in very competitive markets. These results highlight the need of raising awareness and developing capacity among regulatory agencies as well as businesses. The research has consequences for policymaking as well, pointing to the need for programs to raise business understanding, provide funding to regulatory bodies, and create safeguards for intellectual property rights. The study adds to our knowledge of how competition legislation affects corporate behavior and offers insightful information that can guide regulatory strategies in developing nations like West Java.